Ethnobotanical Study on Plants Used As Natural Dye by Handwritten Batik Craftsmen in Cirebon Indonesia - Jabar, Muhammad Abdul; Rahayu, Enni Suwarsi; Ramasamy, Sujatha (Biosaintifika: Journal of Biology & Biology Education, 2024)
Cirebon Regency is one of the few Indonesian batik craft center which still use natural dyes in hand-written batik making. The natural dyes are generally extracted from plants. The kind of plants used as natural dyes source for batik in Cirebon Regency are not yet known. This ethnobotanical research aimed to describe the kinds of plants and their characteristics, the frequency of citation by respondents, the parts of the organs used, the sources of obtaining plants, the colors produced, usage technique, as well as the role of using natural dyes in batik to support implementation of green economy. The research approach was exploratory descriptive through observation and interview techniques for data collection. The research was carried out at Kebon Gedang Block, Ciwaringin Village, Cirebon Regency, Indonesia in September 2023. Thirty respondents were selected by purposive sampling method and subjected to the interview. The results showed there were 14 plants species from 12 families used as natural dyes. The most frequently used species were Mangifera indica and Indigofera tinctoria. The organ most widely used was the bark which comes from the purchased, and the color generally produced was brown. The most frequently coloring method used was boiling technique. This research is the first study in this area and useful for providing data and strategic potential for developing local plants as environmentally friendly natural dyes, as well as supporting efforts to use natural dyes in the batik industry.